Adopting microblogging solutions for interaction with government: survey results from Hunan province, China. (March 2022) - Homburg, Vincent; Moody, Rebecca; Yang, Qiaomei; Bekkers, Victor
Authorities in the People's Republic of China communicate with citizens using an estimated 600, 000 Sina Weibo microblogs. This study reports on a study of Chinese citizens' adoption of microblogs to interact with the government. Adoption results from trust and peer pressure in smaller-network ties (densely knit, pervasive social networks surrounding individual citizens). Larger-network ties (trust in institutions at large, such as the Chinese Communist Party, executive organizations, the judicial system, the media, etc.) are not associated with the adoption of microblogging. Furthermore, higher levels of anxiety are correlated with lower levels of use intention, and this finding underlines the impact of the Chinese authority's surveillance and control activities on the lives of individual Chinese citizens. Based on these findings, we outline a theory of why citizens use microblogs to interact with the government and suggest avenues for further research into microblogs, state–citizen communication patterns and technology adoption. Points for practitioners: Our research identifies trust in individual civil servants, citizens' anxiety and peer pressure as drivers of Chinese citizens' intentions to use the Weibo microblogging platform to interact with the Chinese government. This insight allows practitioners to better understand citizens' drivers and obstacles in the use of social media in state–citizen relations in China.